Professional dilemmas for caregivers in Turkish home care settings in Germany - Basche, Jan (Border Crossing, 2014)
While calling for culturally sensitive healthcare services in migrant communities, the international nursing literature on intercultural care predominantly describes nursing staff as lacking cultural competences and immigrant customers as lacking cleverness to navigate the labyrinths of national healthcare systems. Congruences in language, culture and religion in the customer-caregiver relationship can decisively improve the quality of care. However, they do not automatically guarantee smooth working processes in monocultural in-home settings. On the contrary, new problems occur here for Turkish caregivers which are unknown to the legions of native professionals who feel challenged by migrants and which go beyond differences such as age, sex, income or education. While no cultural or religious brokering is necessary between customers and personnel in the given context in Germany, new challenges arise when caregivers are expected to legally broker between customers and insurance companies or doctors. Conflicting expectations of customers and management as well as their own colliding social and professional roles put the caregivers in a quandary and must be competently managed.